Postoperative swallowing recovery in oral and oropharyngeal cancer: A prospective analysis of functional changes and adjuvant therapy effects - Loan Thi Hong Nguyen; Duc Tan Vo; Truc Thanh Thai; Xuan Quang Ly (PLoS ONE, 2026)
Dysphagia is a prevalent and debilitating sequela in patients with oral cavity and oropharyngeal cancers undergoing surgery, often complicated by adjuvant radiotherapy or chemoradiotherapy. This prospective cohort study aimed to describe the longitudinal changes in swallowing and oral intake and assess the influence of adjuvant treatment modalities. We included 89 patients with oral cavity or oropharyngeal squamous cell carcinoma. Swallowing was assessed at 1, 3, and 6 months post-surgery using Eating Assessment Tool-10 (EAT-10), Swallowing Ability and Safety Scale (SASS), Functional Oral Intake Scale (FOIS), and Fiberoptic Endoscopic Evaluation of Swallowing (FEES). Patients were stratified by adjuvant treatment: none, radiotherapy, or chemoradiotherapy. Swallowing recovery was dynamic. EAT-10 scores increased from 8.8 at 1 month to peak at 13.5 at 3 months (p < 0.001), before decreasing to 8.3 at 6 months (p < 0.001). Penetration/aspiration for thin liquids significantly increased from 32.6% at 1 month to 44.9% at 3 months (p = 0.034), then decreased to 31.5% at 6 months (p = 0.014). FOIS and SASS scores showed overall improvement from 1 to 6 months (p < 0.001 for both), despite a transient dip in FOIS and a rise in poor SASS scores at 3 months. Patients receiving chemoradiotherapy demonstrated greater perceived dysphagia, lower functional oral intake, and higher rates of thin liquid penetration/aspiration compared to other groups across all time points. In conclusion, chemoradiotherapy is associated with more severe and prolonged dysphagia. These findings underscore the critical need for targeted rehabilitation and comprehensive multidisciplinary care.